Effect of Processing Followed by Fermentation on Antinutritional Factors Content of Pearl Millet (Pennisetum glaucum L.) Cultivars - Eltayeb, Mohamed M.; Hassn, Amro B.; Sulieman, Mashier A.; Babiker, Elfadil E. (Pakistan Journal of Nutrition, 2007)
Two pearl millet cultivars (Gazira and Gadarif) were processed (grinding, soaking, autoclaving, germinating and debranning). The processed grains were fermented for 12 and 24hrs. Phytic acid, polyphenols and tannin contents were determined. Results obtained showed that phytic acid content was 987.19 and 952.51 mg/100g for Gazira and Gadarif cultivars, respectively. Processing treatments were observed to decrease phytate content significantly (P = 0.05) for both cultivars with a maximum reduction observed when the grains of the cultivars were germinated. Polyphenols and tannin were also decreased significantly after processing of both cultivars. Further reduction in antinutritional factors was obtained when the processed grains were fermented for 12 and 24 hrs. The rate of reduction differs between the cultivars and the processing treatments.